New onset diabetes after kidney transplantation is associated with increased mortality—A retrospective cohort study. Issue 8 (30th August 2017) - Cooper, L.; Oz, N.; Fishman, G.; Shohat, T.; Rahamimov, R.; Mor, E.; Green, H.; Grossman, A.
Abstract: Objective: Clinical outcomes in individuals with new onset diabetes after transplantation (NODAT) and the optimal treatment for this complication are poorly characterized. This study was intended to better define these issues. Methods: Patients who underwent kidney transplantation and did not have diabetes prior to transplantation were included in the study. Clinical outcomes were compared between those who developed NODAT and those who did not. In those who developed NODAT, oral therapy was compared with insulin based therapy. Results: A total of 266 kidney transplant recipients were included, of which 71 (27%) developed NODAT during the time of the follow‐up. Using Cox multivariate analysis adjusted for age and gender, hazard ratio for overall mortality among patients with NODAT versus those without NODAT was 2.69 (95% CI 1.04‐7.01). Among patients who developed NODAT, 29 patients (40%) were treated with an insulin‐based regimen. At the end of follow‐up, no difference was found in mean HbA1c, and therapy regimen was not associated with greater mortality. Conclusions: New onset diabetes in kidney transplanted patients is associated with increased mortality compared with kidney transplanted patients without NODAT.